Pemberdayaan Masyarakat dalam Berwirausaha Produk Hasil Pertanian Dimasa Pendemi Covid 19 - Rusnani Rusnani; Sri Harimurti; Epit Erwandri; Enita Enita (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
The Covid 19 pandemic that occurred in Indonesia since the beginning of March 2020, resulted in several business activities being suspended, mass layoffs, decreased people's income, and the people's purchasing power for goods also decreased. Based on the results of the analysis of The Economist Intelligence Unit (EIU) in April 2020, it shows that the growth of the manufacturing sector was 3.0% to -1.5% (corrected -4.5%) and the service sector 7.2% to 2.4% (corrected -4.8%), sector growth agriculture was only revised from 4.1% to 3.2% (corrected-0.9%). This shows that the Covid 19 pandemic has the least impact on businesses in the agricultural sector so that entrepreneurial opportunities in the agricultural sector are still large. In the Teratai village, Muara Bulian district, Batang Hari Regency, Jambi Province, most of the entrepreneurs owned by the residents are processed agricultural products in the form of snacks such as various cakes, chips, bread, and side dishes. Through community service activities in the form of counseling and assistance for entrepreneurial management, it can encourage people to develop businesses and manage a business with good management. The survey results showed that 66.67% experienced a decrease in demand for products offered during the Covid 19 pandemic and 33.33% demand for products offered remains the same as before the Covid 19 pandemic. The causes of decreased demand among others are a lack of knowledge of changes in consumer behavior, limited space due to the Covid 19 pandemic, and a lack of technological knowledge to market products.